منهج الإمام محمّد ين يوسف السّنوسي(ت895ه) في عرض علمي الحديث واللغة من خلال كتابه مكمّل إكمال الإكمال - حنانشة, مصطفى; بوغزالة, محمّد رشيد (جامعة الوادي - University of Eloued, 2020)
يتمحور الكلام في هذه الورقة البحثيّة على ما اشتهر عند العلماء المغاربة بـ "الإكمالات" على الشّروحات السّابقة مع إثباتها في الشّرح المتأخر وتسمية الكتاب بالإكمال أو المكمل اعترافا بفضل السّابق وتواضعا من اللاحق وإكمالا لمجهوده, ومثّلت بكتاب الإمام مسلم وما تمّ شرحه بهذه الطٍّريقة مع الإشارة لأغلب مَن تناوله من المغاربة, معرفا باسم الكتاب وصاحبه, وخصّصت لمن تسلسل تتابعهم حتّى الإمام السّنوسي لمحة عن مناهجهم والعلوم التي تكلموا فيها مع التّمثيل ثم عرّفت أحد أعلام تلمسان الإمام محمّد بن يوسف السّنوسي باختصار,ثمّ تناولت منهج الإمام السّنوسي في كتابه مكمّل إكمال الإكمال, فذكرت منهجه في عرض علوم الحديث رواية ودراية وكيفية عرضها في ثنايا شرحه, فاخترت عناوين تفصيليّة لعدّة موضوعات حديثيّة, كتعريف الحديث الصّحيح و الحسن و الضّعيف و أنواعه, قضايا الجرح و التّعديل بمختلف جزئياتها, وبيّنت نقله باللفظ وأمانته, ونقله بالمعنى أو الاختصار, وطرح مختلف الآراء وبراعته في مناقشته والتّرجيح بينها بأدلة ناصحة, مع الرّجوع في كلّ فن لأهله مع التّسليم التّام لهم, وعرّجت على طريقة شرحه بنسبة الأقوال لأصحابها مع التّرميز لهم كما وعد في مقدمته, مع عدم مراعاة زمن الشّرّاح بل حسب نسق الكلام وشروحاتهم, وتوضيح الغامض منها, ثمّ موافقتهم أو الاعتراض عليهم, وإيراد التّساؤلات والجواب عليها, ثمّ عرضت منهجه في اللغة, فبيّنت تمكّنه منها, وبراعته في عرضها واستثمارها في شرح السّنن مع ضبط الكلمات وإعرابها واستثمار البلاغة بالإيجاز أو الحذف لشرح الحديث وإثبات مختلف الرّوايات الحديثيّة وتوجيهها لغويّا, وختمت الورقة بذكر أهم النّتائج التي توصلت إليها وهي براعة هذا الإمام في شرحه بعرض علم الحديث واللغة بما يخدم الشّرح, والإطناب أحيانا والاختصار الشّديد أحيانا أخرى حسب ما يقتضيه المقام, وأوصينا بتحقيق كتابه الماتع والحافل بعلوم شتى. Abstract: The speech in this research paper focuses on what is known to Moroccan scholars as "completions" on the previous explanations with their confirmation in the late explanation and naming the book as completion or complementary in recognition of the former thanks and humility of the later and to complete his effort, and was represented by the book of Imam Muslim and what was explained in this way with The reference to most of the Moroccans. Identifying the name of the book and its author, and was devoted to those whose sequence to Imam Al-Senussi is a glimpse of their methods and the sciences in which they spoke on with the representation. Then briefly defined one of the scholars of Tlemcen Imam Muhammad ibn Yusuf al-Sanusi in a nutshell, then I dealt with the approach of the Imam Al-Sunnah In his book,supplementing the completion of complementary. I mentioned his method in presenting modern sciences telling and knowing in addition to how to display it in the folds of his explanation, so I chose detailed titles for several modern topics, such as the definition of true and good and weak and modern types of All-Hadith , wound issues and modification in its various parts, and indicated its transfer by word and its integrity And convey it in the sense or pithiness, and put forward various opinions and his proficiency in discussing and telling them with clear guides, with referencing in every art to his family with complete surrender to them, and I approached the way of explaining it in proportion to the statements of their owners with the coding for them as promised in his introduction, with no observance of the explanation time, but according to Organize speech and explanations, and He clarified the mysterious ones, then agreed with them or objected to them, and mentioned the questions and the answer to them, then I presented his method in the language, so he demonstrated his mastery of it, his skill in displaying it and investing it in explaining the Sunnah with controlling the words and their expressions and investing the rhetoric by briefly or omitting to explain the modern and prove the various modern narrations and guide them linguistically, The paper concluded by mentioning the most important results that it reached, which is the ingenuity of this imam in his explanation by presenting the science of hadith and language to serve the explanation, and sometimes redundancy and severe shortening at other times as required by the place, and we recommended the realization of his bright book full of various sciences. Key words: Complementary Completion, Senussi, Hadith Sciences
مقال في مجلة الشهاب بجامعة الوادي
Keywords: مكمّل الإكمال, السّنوسي, علوم الحديث